Chronic variable stress alters hypothalamic-pituitary-adrenal axis function in the female mouse - Borrow, Amanda P.; Heck, Ashley L.; Miller, Alex M.; Sheng, Julietta A.; Stover, Sally A.; Daniels, Renata M.; Bales, Natalie J.; Fleury, Theodore K.; Handa, Robert J. (Physiology & behavior, 2019)
Chronic stress is often associated with a dysregulation of the hypothalamic-pituitary-adrenal (HPA) axis, which can greatly increase risk for a number of stress-related diseases, including neuropsychiatric disorders. Despite a striking sex-bias in the prevalence of many of these disorders, few preclinical studies have examined female subjects. Hence, the present study aimed to explore the effects of chronic stress on the basal and acute stress-induced activity of the HPA axis in the female C57BL/6 mouse. We used a chronic variable stress (CVS) paradigm in these studies, which successfully induces physiological and behavioral changes that are similar to those reported for some patients with mood disorders. Using this model, we found pronounced, time-dependent effects of chronic stress on the HPA axis. CVS-treated females exhibited adrenal hypertrophy, yet their pattern of glucocorticoid secretion in the morning resembled that of controls. CVS-treated and control females had similar morning basal corticosterone (CORT) levels, which were both significantly elevated following a restraint stressor. Although morning basal gene expression of the key HPA-controlling neuropeptides corticotropin releasing hormone (CRH), arginine vasopressin (AVP) and oxytocin (OT) was unaltered within the paraventricular nucleus (PVN) by CVS, CVS altered the PVN OT and AVP mRNA responses to acute restraint. In control females, acute stress decreased AVP, but not OT mRNA; whereas, in CVS females, it decreased OT, but not, AVP mRNA. Unlike the morning pattern of HPA activity, in the evening, CVS-treated females showed increased basal CORT with hypoactive responses of CORT and PVN c-Fos immunoreactivity to restraint stress. Furthermore, CVS elevated evening PVN CRH and OT mRNAs in the PVN, but it did not influence anxiety- or depressive-like behavior after a light/dark box or tail suspension test. Taken together, these findings indicate that CVS is an effective model for HPA axis dysregulation in the female mouse and may be relevant for stress-related diseases. •Female mice exhibit time-dependent HPA axis dysregulation after chronic stress.•Chronic stress alters the morning responses of hypothalamic mRNAs to acute stress.•Chronic stress changes evening basal and acute stress-induced corticosterone levels.